Renewable Energy Fed Bidirectional Converter Based on Grid Application Using Fuzzy Logic-PID Controller - et.al, Kalluri Venkateswarlu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Photovoltaic systems containing rechargeable batteries as a power buffer takes extensive DC-DC converters for photovoltaic panel control and battery regulation. This paper suggests the non-isolated bidirectional fed grid for stand-alone pv systems in order to simplify the operation by reducing the number of transformers. In the bidirectional converter suggested, the power is transmitted from the solar to the grid. Then lack of PV power; back up storage that is battery supplies power. Fuzzy PID control is used to controls the voltage of DC along with increases the gain of voltage by means of a bidirectional converter. The proposed bidirectional converter implemented and the simulations are observed in MATLAB / Simulink.